SOROLOGICAL INQUIRY FOR DETECTION OF Toxoplama gondii ANTIBODIES IN GOATS (Capra hircus) RAISED IN GRAVATAÍ AND VIAMÃO COUNTIES, RIO GRANDE DO SUL, BRAZIL - Maciel, Karen Praetzel; Araujo, Flavio Antonio Pachaeco de (Revista de Ciências Agroveterinárias, 2004)
Toxoplasmosis is one of the most widespread transmissible parasite infection diseases. The aim of this work was to evaluate the role of the goats in Toxoplasma gondii transmission.The sampling was stratified by age and gender. Three hundred and sixty (360) goat sera samples were tested by Indirect Hemagglutination technique (IHA) and Indirect Immunofluorescence test (IIF). The results showed that 19,4% (70 animals) of the sera samples were positive to IHA and 30,0% (108) were positive to IIF, representing a high level of sera positivity. Results of IHA associated to the variable gender showed 9,44% (34) sera positive for male goats and 10,0% (36) for female, whereas the results associated to the variable age showed frequencies of 3,05% (29) for young goats and 11,38% (41) for adults. The IIF results for to the variable gender showed a frequenct of 14,44% (52) positivity for males and 15,56% (56) for females. Using the same technique to evaluate the variable age, a soropositivity frequency of 13,06% (47) for young goats and 16,94% (61) for adults was recorded. The two techniques used were compared and the data obtained showed a significant association between them, with a copositivity rate with IHA of 78,6% and conegativity of 81,7%. The Kappa index used to measure the real agreement among the two techniques was 0,5%, indicating a moderate agreement level. Therefore, the results recommend caution for the use of IHA in goats.